Gamifikasi, Pemasaran di Era Digital: Studi pada Pengguna Game Fantasy Premier League di Indonesia - Arif Taufiq Nugroho (Jurnal Riset Komunikasi, 2021)
Technological developments have affected various fields, including marketing. Gamification as the result of the development of digital technology that combines business management strategies, game dynamics, and computer programming is then applied by the Premier League in their game, Fantasy Premier League (FPL). This study explored how FPL is seen from a marketing perspective through user experience in Indonesia. The research uses a qualitative approach with phenomenological methods and purposive sampling technique. The samples studied are four FPL users. The data were obtained through observation and semi-structured interviews which were then processed through a coding process. The results show that the FPL users’ experience generates intrinsic motivation to watch the English Premier League and to invite others to also play FPL. From this research, it can generally be concluded that FPL increases Purchase, Engagement, Advocate, and Brand Awareness of the English Premier League. Gamification in the FPL has practiced marketing 4.0 to strengthen their online and offline relationships between customers.